Testing an indirect method for identifying galaxies with high levels of Lyman continuum leakage. Issue 3 (20th August 2020) - Yamanaka, Satoshi; Inoue, Akio K; Yamada, Toru; Zackrisson, Erik; Iwata, Ikuru; Micheva, Genoveva; Mawatari, Ken; Hashimoto, Takuya; Kubo, Mariko
ABSTRACT: Using a sample of galaxies at z ≈ 3 with detected Lyman Continuum (LyC) leakage in the SSA22 field, we attempt to verify a proposed indirect method for identifying cases with high LyC escape fraction f esc based on measurements of the H β equivalent width (EW) and the β slope of the UV continuum. To this end, we present Keck/MOSFIRE H β emission line flux measurements of LyC galaxies (LCGs) at spectroscopic redshifts z spec ∼ 3.3, Lyman break galaxies (LBGs) at photometric redshifts z phot  = 2.7–3.7, and Ly α emitters at z phot  = 3.1. We also reconfirm the spectroscopic redshifts and measure the H β emission-line fluxes from two LCGs and six LBGs. For the LCG in our sample with the most extreme f esc, as revealed by the direct detection of LyC photons, we find that the EW(H β)–β method gives a broadly consistent estimate for f esc, although the error bars remain very large. We also discuss how a combination of f esc measurements based on direct and indirect methods can shed light on the LyC escape mechanism and the anisotropy of the leakage.